Participation in the anti-sexual violence silent protest: a sexual citizenship perspective - Chitiki, Elizabeth (Rhodes University, Faculty of Humanities, Department of Psychology, 2018)
There is a growing body of research on sexual citizenship that focuses attention on gender and which bridges the gap between public and private life in order to rethink citizenship from a feminist perspective. This is in contrast to understandings of citizenship that promote policies of sexual regulation and a heteronormative ideal of citizenship. My research takes the form of a qualitative case study. Using data from two focus group discussions, fifteen personal diaries, as well as social media posts, I analyse participation in the Silent Protest, an annual anti-rape protest, through the lens of sexual citizenship. I look at how participation in the protest promotes or inhibits inclusive and process-based understandings of sexual violence and sexualities issues. Data were analysed using thematic analysis and the results of the analysis are presented into two parts. The first part of the analysis discusses the politics of affect and witnessing as two processes through which allies' understandings of sexual violence are shaped. The second part of analysis shows that the Silent Protest contributes to people's knowledge and understandings of sexual violence in relation to sexualities in a range of ways. Examples of inclusive understandings are: (1) insights about rape in relation to gender and heteronormative inequalities, culture and patriarchal dominance; (2) understanding of critical sexual citizenship in relation to sexual violence; and (3) understanding of politics of recognition (the need for recognition of the importance of safe spaces for formal and informal support for victim-survivors and recognition of victim-survivors' identities). However, some of the understandings are limited to emotion and affect dynamics. In some ways, therefore, the Silent Protest fails to promote understandings significant to inclusive citizenship, including understandings of entitlements to non-discriminatory sexual health care services and legal services.
Keywords: Sex crimes; Campus violence -- South Africa -- Prevention; Rape victims -- Services for -- Political aspects -- South Africa; Anti-rape movement; Rape -- Case studies; Sexual orientation